Creative Music Therapy and Neurodevelopmental Outcomes in Pre-term Infants at 2 Years: A Randomized Controlled Pilot Trial - Friederike Barbara Haslbeck; Hans Ulrich Bucher; Dirk Bassler; Cornelia Hagmann; Cornelia Hagmann; Giancarlo Natalucci; Giancarlo Natalucci (Frontiers Media S.A., 2021)
Impaired neurodevelopment is increasingly recognized as a major health issue in children born prematurely. Creative music therapy (CMT) intends to prevent and or reduce neurobehavioral deficits in pre-term infants using musical stimulation and socio-emotional co-regulation. We conducted a randomized, clinical pilot CMT trial to test feasibility and to examine long-term neurodevelopmental outcomes in pre-term infants (NCT02434224: https://clinicaltrials.gov/ct2/show/NCT02434224). Eighty-two pre-term infants were randomized either to CMT or standard care. A specially trained music therapist provided family-integrating CMT via infant-directed singing during hospitalization. Fifty-six infants underwent follow-up at 2 years of corrected age. No significant beneficial nor adverse effects of CMT were identified in routine clinical neurodevelopmental measures (Bayley-III Scales of Infant and Toddler Development and the standardized neurological examination). Longer term follow-up (5 years) and larger future studies are recommended to elucidate possible long-term effects of music in relation to more sensitive outcomes including executive function, detailed language processing and social-emotional development.